2010
DOI: 10.1016/j.ecl.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Type 1 Diabetes

Abstract: Synopsis This chapter describes the epidemiology of type 1 diabetes mellitus (T1D) around the world and across the lifespan. Epidemiologic patterns of T1D by demographic, geographic, biologic, cultural and other factors in populations are presented to gain insight about the etiology, natural history, risks, and complications of T1D. Data from large epidemiologic studies worldwide indicate that the incidence of T1D has been increasing by 2–5% worldwide and that the prevalence of T1D is approximately 1 in 300 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
723
3
40

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 972 publications
(786 citation statements)
references
References 124 publications
20
723
3
40
Order By: Relevance
“…Earlier results from the SCDR showed that 91.5% of the children had no parent with insulin-dependent diabetes, compared with 98.9% among the reference group [20]. In this study sample, boys and children with parents born in a Nordic country had a higher risk of diabetes (ESM Table 7), in accordance with previous studies on the incidence of type 1 diabetes [21,22]. In the regression analyses, we adjusted for these variables.…”
Section: Discussionsupporting
confidence: 75%
“…Earlier results from the SCDR showed that 91.5% of the children had no parent with insulin-dependent diabetes, compared with 98.9% among the reference group [20]. In this study sample, boys and children with parents born in a Nordic country had a higher risk of diabetes (ESM Table 7), in accordance with previous studies on the incidence of type 1 diabetes [21,22]. In the regression analyses, we adjusted for these variables.…”
Section: Discussionsupporting
confidence: 75%
“…T1DM currently constitutes 5 to 10% of all people with diabetes globally (66,67). GM is one of the essential elements of effective T1DM management (68,69).…”
Section: Gm Strategy and Rationale By Patient Profile T1dmmentioning
confidence: 99%
“…Better GC is associated with improved survival in patients with T1D, leading to progressive changes in the causes of mortality, particularly cardiovascular disease; therefore, it is important to identify the risk factors for cardiovascular disease in this population (25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%